INITIAL CREATIVEPRENEUR THROUGH CREATIVITY BASED COMMUNITY SERVICES: INITIAL CREATIVEPRENEUR THROUGH CREATIVITY BASED COMMUNITY SERVICES - Dewanti, Paula; Permana, Putu Adi Guna (IKRA-ITH ABDIMAS, 2018)
ABSTRACT Known for its distinctive art, Bali declared as one of the main tourist destinations of Indonesia. Painting is one of them, in addition to carving, dance and many other arts. Besides canvas as a medium of painting, Balinese artists also use other media to express their artwork. In this Community Service, the author highlighted artisans of wooden egg painting, located in Banjar Gerih, Batuan Village, District Sukawati, Gianyar, Bali, Indonesia. Gianyar Regency, itself, well-known as the centre of art. Based on the problems encountered, the use of online media, were taken as an alternative solution to streamline marketing as well as increase number of product sales. Performance indicator is a 100% increase in partner revenue; creating an online marketing accounts at one of online marketplace and able to maintain the account.